Studi Komparasi Penerapan Model Guided Discovery Learning dan Inquiry Learning terhadap Retensi Matematika - Lilik Masfiyah; Rufi'i Rufi'i; Harwanto Harwanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
This study aimed to examine the differences in mathematics retention of grade V Primary school between students who were taught using guided discovery learning model and inquiry learning model. The method in this study was a quasy experimnetal method. The population in this study was all students in grade V at SDN Pongangan and SDN Sukomulyo in 2018/2019 academic year which in total were 202 students. Samples were selected by purposive random sampling. The sample was divided into two group which are experiment 1 and experiment 2. The instrument used to collect mathematics retention data was a written test. The Data was analysed using descriptive statistic analysis and t-test. The results of data analysis at 0,05 significance level and df = 130 showed that t-count (2,276) > t-tabel (1,978) and also p-value (2-tailed) 0,024 < 0,05. So, it mean that there was a significant difference in mathematics retention between students who were taught using guided discovery learning model and inquiry learning model.